Students Perception of Project-Based Vlogging Through Descriptive Text in Developing Speaking Skill in Thai Secondary School - Salwa Azzahra; Khairun Nissa (Continuous Education: Journal of Science and Research, 2026)
This study explores Thai secondary school students’ perceptions of project-based vlogging through descriptive text in developing English speaking skills. Speaking is widely regarded as one of the most challenging skills for English as a Foreign Language (EFL) learners due to affective factors such as anxiety, limited exposure to English, and low confidence in oral communication. To address these challenges, this study integrates project-based learning with digital vlogging activities supported by descriptive text as a planning scaffold for speaking. The study employs a mixed-method case study design with a qualitative-dominant orientation involving 25 Grade 11 students at a Thai secondary school. Data are collected through classroom observation, semi-structured interviews, documentation, and a Likert-scale questionnaire. Students’ perceptions are examined across four dimensions: selective perception, subjective evaluation, external social factors, and responses and intentions. Qualitative data are analyzed thematically to capture students’ experiences and interpretations, while quantitative data are analyzed descriptively to identify general perceptual trends. The findings are expected to provide insights into how students experience, evaluate, and respond to project-based vlogging activities through descriptive text as part of EFL speaking instruction. This study contributes to a deeper understanding of learners’ subjective experiences and social influences in technology-integrated speaking activities within secondary school EFL contexts.